Amorphous NiO electrocatalyst overcoated ZnO nanorod photoanodes for enhanced photoelectrochemical performance. (28th October 2015) - Mao, Yanchao; Cheng, Yongguang; Wang, Junqiao; Yang, Hao; Li, Mingyang; Chen, Jian; Chao, Mingju; Tong, Yexiang; Liang, Erjun
Abstract : This research demonstrated that introducing amorphous NiO electrocatalysts onto the surface of ZnO photoanodes can effectively facilitate their PEC performance. Abstract : Developing high-performance photoanodes is essential for practical applications of photoelectrochemical (PEC) water splitting. In this work, we demonstrated that introducing amorphous NiO electrocatalysts onto the surface of ZnO nanorod (NR) photoanodes can largely improve their PEC performance. The NiO/ZnO core–shell NR arrays were obtained by two step electrodepositions and annealing. The amorphous NiO nanosheet electrocatalyst shell on a single crystalline ZnO NR semiconductor core formed a composite photoanode configuration for PEC water splitting. The NiO/ZnO photoanode yielded a remarkable 260 mV cathodic shift in the onset potential for water oxidation compared to the bare ZnO photoanode. And the highest PEC efficiency of the NiO/ZnO photoanode was found to be 1.81%, which is 30 times higher than that of the ZnO photoanode (0.06%). This research demonstrates that introducing amorphous NiO electrocatalysts can largely improve the PEC performance of ZnO photoanodes.